STRESS LEVELS AMONG UNDERGRADUATE MEDICAL STUDENTS ON EXPOSURE TO ONLINE LEARNING - Sanian Inama; Yuke Sarastri (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: Adolescence is a time of significant psychosocial and physiological changes, such as changes in the reactivity of the hypothalamic-pituitary-adrenal (HPA) axis, which causes an increase in stress-induced hormonal responses. Mental health disorders in medical students are often reported. Moreover, during the COVID-19 pandemic, most medical schools have changed the pre-clinical learning curriculum to online learning, hence most of the student's needs cannot be fulfilled. This study aims to determine the overview of the stress level among undergraduate medical students in Indonesia on exposure to online learning.Methods: This research uses a descriptive cross-sectional design. The primary data was taken with Medical Student Stressor Questionnaire, with undergraduate medical students, especially semester III-VII, as the target population. The minimal population was calculated using a stratified random sampling technique. Data were analyzed using the descriptive method.Results: In this study, most of the students experienced moderate stress (49.1%). Based on their age, the highest stress level was found in students aged 20 years (37%). Based on their gender, a higher stress level was found in female students (61.1%), compared to male students (38.9%). Based on the year, the highest stress level was found in the class of 2019 students (35.2%).Conclusion: Most of the students of the Faculty of Medicine in Indonesia experienced moderate stress during online learning. There is no significant difference between the stress levels of undergraduate medical students before and after the implementation of the online learning system